Effect of a carbohydrate drink on soccer skill performance following a sport-specific training program - O'Reilly, J.; Wong, S. H. (Journal of Exercise Science & Fitness, 2013)
Monitoring personal hydration status as well as examining the contents of sports beverages is crucial to improve physical performance in soccer players. This study examined the effects of 60 minutes of soccer-specific training on skill performance, hydration status, and core temperature (Tc) of soccer players after ingesting either a carbohydrate-containing (CHO) or a carbohydrate-free (CHO-F) drink. This study recruited seven healthy male soccer players (age: 23 ± 2.9 years, height: 1.7 ± 0.04 m, mass: 62.7 ± 6.7 kg), each of whom completed a CHO and a CHO-F trial in a randomized crossover design. The participants underwent skill tests [Loughborough Soccer Passing Test (LSPT)] prior to and after 60 minutes of training in a hot and humid environment (30 °C, 85% relative humidity). They consumed 2 mL of fluid per/kg body mass every 15 minutes during exercise. Blood glucose, blood lactate, and Tc were monitored throughout the exercise session. Improvement was observed in movement time (p = 0.034) and overall LSPT performance (p = 0.031) postexercise in those consuming CHO drinks compared with those consuming CHO-F drinks. No differences were observed in Tc or absolute and relative body mass loss between the trial groups (p > 0.05). Urine output was greater in the CHO trial group (CHO: 0.086 ± 0.051 L; CHO-F: 0.030 ± 0.028 L; p = 0.043). Compared with the consumption of a CHO-F drink, that of a CHO drink during a 60-minute soccer-specific exercise session in a hot and humid climate can improve postexercise skill performance. Additionally, Tc can be regulated efficiently by commencing training in a state of euhydration and by regular ingestion of fluids throughout the exercise period.